Care Cage: Black Women, Political Symbolism, and 1970s Prison Crisis. Issue 1 (2nd January 2018) - Haley, Sarah
Abstract : Mary Fitzpatrick's historical life sheds light on the role of liberal discourse and racialized and gendered affective politics in entrenching black captivity. Her imprisonment and coerced domestic servitude reveal the role of black women's carceral exploitation in a pivotal 1970s moment in which the future of the U.S. carceral state was contested and contingent.